A Christian-Based Counseling Model in Education: A Conceptual Framework - Amanatidis, Nikolaos (Academia Publication, 2026)
This article explores the integration of counselling within educational frameworks through the lens of Christian pedagogy and edification, focusing on its role in the holistic development of educators and students in Eastern Thessaloniki, Greece. The study aims to outline how Christian values can be effectively integrated into counselling practices to address personal, pedagogic, and social challenges such as bullying and interpersonal conflicts encountered in modern school reality. Utilizing a research methodology that synthesizes existing literature with Christian pedagogical strategies, the study proposes the